Mucosal Immunology of Acute Bacterial Pneumonia - Prince, Alice.; Prince, Alice. (Springer New York : Imprint: Springer, 2013)
In contrast to the substantial literature that focuses upon innate immune signaling in the gut, there is remarkably less known about the response of the airway to bacterial pathogens.  The purpose of this book will be to review the current status of theunderstanding of the pathogenesis of acute bacterial pneumonia, slanted toward the mucosal immunology of these infections.  It will describe, in general, the signaling cascades that control the proinflammatory response to bacterial infection in the lung. How innate immune signaling is orchestrated in response to specific common airway pathogens is addressed, targeting Staphylococus aureus (including MRSA), Streptococcus pneumoniae and Klebsiella pneumoniae.   By describing the general immunological responses to conserved bacterial components and then detailing how specific organisms cause infection, this book provides a targeted but comprehensive review of this important topic.